2014
DOI: 10.1111/aas.12297
|View full text |Cite
|
Sign up to set email alerts
|

Veno-venous extracorporeal membrane oxygenation in obese surgical patients with hypercapnic lung failure

Abstract: ECMO in obese patients is feasible and life saving. Therefore, a percutaneous cannulation remains feasible. The goals of the ECMO therapy include early spontaneous breathing, tracheotomy, rapid reduction of sedation and adequate analgesia. Rehabilitation includes nutritional therapy, as well as psychiatric therapy and bariatric surgery, as perspectives for the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 17 publications
(18 reference statements)
3
26
0
Order By: Relevance
“…These case reports showed that extracorporeal lung support is a feasible treatment option for extremely obese patients with ARDS, a finding that was previously described [9,10]. After weaning from ECMO, 1 patient required noninvasive ventilation support; the other died of multiorgan failure due to secondary sepsis.…”
Section: Obesity (Body Mass Index [Bmi]mentioning
confidence: 61%
See 1 more Smart Citation
“…These case reports showed that extracorporeal lung support is a feasible treatment option for extremely obese patients with ARDS, a finding that was previously described [9,10]. After weaning from ECMO, 1 patient required noninvasive ventilation support; the other died of multiorgan failure due to secondary sepsis.…”
Section: Obesity (Body Mass Index [Bmi]mentioning
confidence: 61%
“…A BMI higher than 40 kg/m 2 seems to be associated with an increased risk of developing acute respiratory distress syndrome (ARDS) along with greater morbidity, length of stay, and duration of mechanical ventilation in the intensive care unit (ICU) [8]. However, extreme obesity is not a risk factor for hospital mortality in patients with acute lung failure and is not a contraindication for venovenous extracorporeal membrane oxygenation (vv ECMO) implantation [9,10]. We report on 2 cases of surgically treated patients (BMI N 70 kg/m 2 ) with postoperative ARDS and ECMO support.…”
Section: Obesity (Body Mass Index [Bmi]mentioning
confidence: 99%
“…The second patient, who had a BMI of 88.6 kg/m 2 , developed severe ARF because of sepsis after treatment of necrotizing fasciitis, and VV-ECMO was indicated [11]. Extreme obesity is not a contraindication for VV-ECMO implantation [1214]. However, treating extremely obese patients with VV-ECMO poses a special challenge for intensivists.…”
Section: Discussionmentioning
confidence: 99%
“…However, treating extremely obese patients with VV-ECMO poses a special challenge for intensivists. Femorojugular venovenous percutaneous cannulation is associated with several pitfalls including difficulty locating the anatomical landmarks and the inability to visualize the blood vessels sonographically [14]. The cannulation procedure must be performed by experienced practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…Extracorporeal membrane oxygenation (ECMO) for lung support was also considered for this patient. Veno-venous ECMO for patients with lung failure has been performed in this ICU since 2008, but clinicians were concerned about the use of ECMO as a rescue option in this case [9]. The use of ECMO to treat PPF has shown promising results in case reports because it can provide a therapeutic bridge to lung-protective ventilation and the remainder of the lung and allows for PPF closure [10][11][12][13].…”
Section: Case Reportsmentioning
confidence: 99%